5 The interchangeability of the 2.4 km run time and multistage fitness test score as performance predictors for phase 2 army recruits completing a 12.8 km loaded march carrying an 11 kg backpack and 4 kg rifle. (December 2018) - Moore, D; Harrison, C; Moore, S
Abstract : Pre-loaded-march fitness tests are implemented continually during a soldier's career. The 2.4 km maximal-effort run protocol and the multistage fitness test (MSFT) protocol are used interchangeably as a surrogate tests prior to a loaded-march. Previous research identified that the 2.4 km run time and MSFT score have a strong correlation, no research examined if they had a similar predictive strength in relation to loaded-march performance. This study aimed to quantify the predictive strength of the MSFT score and 2.4 km maximal-effort run time for performance in a 12.8 km 15 kg loaded-march and if the MSFT and 2.4 km maximal-effort run can be used interchangeably with the same predictive strength alongside strength tests and anthropometric measurements from current Army protocols. Testing was completed over eight-days with phase-two British Army recruits from the Royal Electrical and Mechanical Engineers (REME) (n = 12 male recruits aged 18–27). Day one involved collection of anthropometric data and completion of the 2.4 km run protocol, on day four the MSFT protocol was completed and on day eight the 12.8 km 15 kg loaded-march protocol was completed with heart-rate (HR) recorded throughout. The MSFT score and 2.4 km maximal-effort run time do not adequately predict the average percentage of estimated HR maximum (average%E-HRmax) during a 12.8 km 15 kg loaded-march (p=-470 and 0.513 respectively). The MSFT score alongside measures of waist circumference (WC), body fat percentage (BF%) and height is a strong predictor of average%E-HRmax during the 12.8 km 15 kg loaded-march (r=−0.668, p=0.049). The MSFT score, WC, weight and BF% showed a statistically significant negative correlation with the average%E-HRmax during the 12.8 km 15 kg loaded march (r=−0.794, p=0.011), the 2.4 km run time, WC, weight and BF% exhibited a statistically significant strong positive correlation in relation to the average%E-HRmax during the 12.8 km 15 kg loaded-march (r=0.726, p=0.027). The MSFT and the 2.4 km maximal-effort run can be used interchangeably alongside measures of BF%, WC and weight to predict 12.8 km 15 kg loaded-march performance. Low BF% and WC suggest that the presence of excess adipose tissue is detrimental to performance during load-carriage. The current Army strength tests have limited significance to load-carriage performance.